AUTISM SPECTRUM DISORDER (ASD) TOPIC TRENDS: BIBLIOMETRIC ANALYSIS USING BIBLIOSHINY - Gusti Fawwaz Setyo; Afandi, Afandi; Wahyuni, Eko Sri (Universitas Kapuas, 2025)
Bibliometric analysis, a scientific study that uses mathematical and statistical methods to analyze literature, was employed to examine the trends in research on Autism Spectrum Disorder (ASD). The present study utilized data from the Scopus database, which included articles and conference papers published between 2014 and 2023. The study aimed to map and analyze the research direction on ASD. The analysis of 3,879 documents revealed several key findings. Firstly, the topic of ASD exhibited an increasing trend each year. Secondly, certain words such as